Mutational spectrum of Korean patients with corneal dystrophy. Issue 6 (10th February 2016) - Chae, H.; Kim, M.; Kim, Y.; Kim, J.; Kwon, A.; Choi, H.; Park, J.; Jang, W.; Lee, Y.S.; Park, S.H.; Kim, M.S.
Abstract : Corneal dystrophy typically refers to a group of rare hereditary disorders with a heterogeneous genetic background. A comprehensive molecular genetic analysis was performed to characterize the genetic spectrum of corneal dystrophies in Korean patients. Patients with various corneal dystrophies underwent thorough ophthalmic examination, histopathologic examination, and Sanger sequencing. A total of 120 probands were included, with a mean age of 50 years (SD = 18 years) and 70% were female. A total of 26 mutations in five genes (14 clearly pathogenic and 12 likely pathogenic) were identified in 49 probands (41%). Epithelial–stromal TGFBI dystrophies, macular corneal dystrophy and Schnyder corneal dystrophy (SCD) showed 100% mutation detection rates, while endothelial corneal dystrophies showed lower detection rates of 3%. Twenty six non‐duplicate mutations including eight novel mutations were identified and mutations associated with SCD were identified genetically for the first time in this population. This study provides a comprehensive characterization of the genetic aberrations in Korean patients and also highlights the diagnostic value of molecular genetic analysis in corneal dystrophies. Abstract :